Productivity and Quality Eggs of Hans Given Various Kinds of Commercial Concentrates - Shultoni, Habib; Indarsih, Budi; Asnawi, Asnawi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The productivity of laying hens in NTB is still very low, especially on the island of Lombok. The low egg production in Lombok is caused by farmers in Lombok generally raising laying hens not following the standards recommended by feed and seed producers. Each feed producer sells its products at varying prices to attract farmers. The varying prices are determined by the formulation of each feed, Laying hens are very sensitive to changes in feed quality, The type of laying hen feed affects the quality, quantity and productivity of eggs. This study aims to obtain information on the level of productivity and quality of eggs from the use of each commercial concentrate circulating in the Lombok market. This study used a Completely Randomized Design with three treatments, namely: First treatment: Mixture of concentrate pattern with code C Second treatment: Mixture of concentrate pattern with code K Third treatment: Mixture of concentrate pattern with code S. The total number of chickens used in this study was 360 chickens that were 19 weeks old with an average body weight of 1,700 grams consisting of 3 treatments and 4 replications. Each treatment consisted of 120 chickens and each replication consisted of 30 chickens. The data obtained were analyzed by Analysis of Variance using Microsoft Excel software and then processed again with the Duncan's test. Feed productivity with code C: 82.75 ± 1.31. k: 88.33 ± 3.73. S: 83.13 ± 0.91. The internal and external quality of the three treatments did not produce significantly different results. The use of concentrate with code K provided the highest productivity, resulting in greater Income Over Feed Cost (IOFC). While the external and internal quality of eggs obtained in this study obtained results that were not significantly different.